Discussion of "Enhanced Predictions for Peak Outflow from Breached Embankment Dams" by Christopher I. Thornton, Michael W. Pierce, and Steven R. Abt - Gupta S.K.; Singh V.P. (My University, 2025)
[No abstract available]